Challenges in Implementing Digital Medical Records in Indonesian Hospitals: Perspectives on Technology, Regulation, and Data Security - Fita Rusdian Ikawati; M. Syauqi Haris (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
The implementation of digital medical records in Indonesian hospitals faces various challenges, especially in terms of technological readiness, inadequate regulations, and data security threats that need to be addressed to ensure efficient and safe healthcare services. This study aims to identify the challenges in Digital Medical Record Implementation from the perspective of technology, regulation, and data security. This study used a systematic literature review research approach guided by the Preferred Reposrting Items for Systematic Review and Meta-Analysis (PRISMA). The results showed that the implementation of digital medical records in Indonesian hospitals faces considerable challenges from three main perspectives, namely technology, regulation, and data security. The technology perspective includes several challenges such as 1) System Interoperability, 2) Privacy, 3) IT Infrastructure Limitations, 4) Implementation Costs and 5) Maintenance and Technology Adoption by Medical Staff. The regulatory perspective includes challenges such as 1) Regulatory Compliance, 2) Patient Data Protection, 3) Validity of Medical Records, 4) Long-term Data Retention and 5) System Interoperability. The data security perspective includes challenges such as 1) Infrastructure Security, 2) Data Encryption, 3) Access Control, 4) Incident Response and 5) Regular Security Audits. Thus, collaborative efforts between the government, hospitals and technology providers are needed to address these challenges and drive safe and effective digital transformation in Indonesia's healthcare sector.